2013
DOI: 10.4018/ijaeis.2013070105
|View full text |Cite
|
Sign up to set email alerts
|

Models of Urban Land Use in Europe

Abstract: The aim of this paper is to examine available homogenous data on urban conversion of land in Western European countries and determine whether they are suitable to make an international comparison between land policies and management behaviour at the local level. This paper provides some results obtained from currently available information, but it stresses major data production criticalities which hinder the performance of comparable and reliable overall statistical studies. Conclusions stress the need for gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…This is basically because of its scale, since CLC includes small polygons in Urban Residential or Non-Urban areas that should be actually allocated to other classes (Diaz-Pacheco and Gutiérrez, 2014). A similar effect occurs in the Italian territory, also characterized by sprinkling, where Romano and Zullo (2013) described that the artificialized area estimated from regional land use maps is 60% higher than the results obtained from CLC. We therefore concluded that CLC-derived data are not suitable to analyse urban land cover changes in the Portuguese territory.…”
Section: Methodsmentioning
confidence: 89%
“…This is basically because of its scale, since CLC includes small polygons in Urban Residential or Non-Urban areas that should be actually allocated to other classes (Diaz-Pacheco and Gutiérrez, 2014). A similar effect occurs in the Italian territory, also characterized by sprinkling, where Romano and Zullo (2013) described that the artificialized area estimated from regional land use maps is 60% higher than the results obtained from CLC. We therefore concluded that CLC-derived data are not suitable to analyse urban land cover changes in the Portuguese territory.…”
Section: Methodsmentioning
confidence: 89%
“…Together with the development of tourism an excessive building up activity is taking place. The hope is that after what happened along the Adriatic coast and following the alarming results of many researches, including the present one, policy-makers may be encouraged to pursue sustainable tourism development (Romano and Zullo, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In last decades a lot of models have been proposed to analyse land use and land cover change (LUCC) (Romano and Zullo 2013;Koomen 2007;Perchinunno et al 2012;Modica et al 2012;Martellozzo 2012;Nolè et al 2014a;Nolè et al 2014b;Cerreta and Poli).…”
Section: A Quantitative Model To Assess and Predict Land Use Changesmentioning
confidence: 99%
“…The characterization and explanation of land-use change trajectories in small and medium-sized cities act as managing scenarios for development strategies for cities and regional assets, as an ex ante condition for cohesion (Bandeira, Coelho, Sá, Tavares, & Borrego, 2011;Hersperger & Bürgi, 2009;Patacchini & Zenou, 2009;Pinhal, 2016;Romano & Zullo, 2013;Rounsevell et al, 2006). Deep changes in land use are common in these cities producing unbalanced occupation rates with complex interactions between environmental and socio-economic factors on land-use change (ET2050, ESPON, 2014;Fahmi, Hudalah, Rahayu, & Woltjer, 2014;Oueslati, Alvanides, & Garrod, 2015;Salvati & Sabbi, 2011;Verburg, Schot, Dijst, & Veldkamp, 2004).…”
Section: Introductionmentioning
confidence: 99%